Feasibility of the 2-point method to determine the load−velocity relationship variables during the countermovement jump exercise - Alejandro Pérez-Castilla; Rodrigo Ramirez-Campillo; John F.T. Fernandes; Amador García-Ramos (Elsevier, 2023)
Purpose: This study aimed to examine the reliability and validity of load−velocity (L-V) relationship variables obtained through the 2-point method using different load combinations and velocity variables. Methods: Twenty men performed 2 identical sessions consisting of 2 countermovement jumps against 4 external loads (20 kg, 40 kg, 60 kg, and 80 kg) and a heavy squat against a load linked to a mean velocity (MV) of 0.55 m/s (load0.55). The L-V relationship variables (load-axis intercept (L0), velocity-axis intercept (v0), and area under the L-V relationship line (Aline)) were obtained using 3 velocity variables (MV, mean propulsive velocity (MPV), and peak velocity) by the multiple-point method including (20-40-60-80-load0.55) and excluding (20-40-60-80) the heavy squat, as well as from their respective 2-point methods (20-load0.55 and 20-80). Results: The L-V relationship variables were obtained with an acceptable reliability (coefficient of variation (CV) ≤ 7.30%; intra-class correlation coefficient ≥ 0.63). The reliability of L0 and v0 was comparable for both methods (CVratio (calculated as higher value/lower value): 1.11-1.12), but the multiple-point method provided Aline with a greater reliability (CVratio = 1.26). The use of a heavy squat provided the L-V relationship variables with a comparable or higher reliability than the use of a heavy countermovement jump load (CVratio: 1.06-1.19). The peak velocity provided the load-velocity relationship variables with the greatest reliability (CVratio: 1.15-1.86) followed by the MV (CVratio: 1.07-1.18), and finally the MPV. The 2-point methods only revealed an acceptable validity for the MV and MPV (effect size ≤ 0.19; Pearson's product-moment correlation coefficient ≥ 0.96; Lin's concordance correlation coefficient ≥ 0.94). Conclusion: The 2-point method obtained from a heavy squat load and MV or MPV is a quick, safe, and reliable procedure to evaluate the lower-body maximal neuromuscular capacities through the L-V relationship.